Manajemen Sistem Pendidikan Perguruan Tinggi Islam di Indonesia: Sistematic Review - Rodin, Rhoni; Hidayah, Jumatul; Endang; Harmi, Hendra; Fakhruddin; Sutarto (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This study aims to comprehensively examine the management of education systems in Islamic higher education institutions in Indonesia using a systematic review approach. Islamic higher education institutions play a strategic role in fostering an excellent generation with strong Islamic character. Therefore, an effective, adaptive, and competitive education management system is essential. The research method used is a systematic review based on the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) protocol. Data were collected through a search of scholarly articles in reputable databases such as Google Scholar, Scopus, and Sinta, using specific inclusion criteria. Thematic analysis was conducted to identify patterns, challenges, and solutions in education management. The findings indicate that the education management system in Islamic higher education institutions in Indonesia faces challenges, including a lack of synergy between government policies, internal management, and societal needs. Furthermore, the implementation of digital technology and the integration of Islamic values into the curriculum are key aspects for improving educational quality. Islamic higher education institutions in Indonesia encounter various challenges in implementing effective and sustainable education management systems. These challenges encompass diverse aspects of management, ranging from government policies and internal management quality to the ever-changing needs of society.